2002
DOI: 10.26719/2002.8.6.706
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and beliefs about HIV/AIDS in Sana’a, Yemen

Abstract: Although HIV prevalence is low in the Republic of Yemen, existing conditions could lead to the rapid spread of HIV/AIDS. Interviewers helped 1033 residents aged 14-49 years from randomly chosen households to complete a survey of knowledge, attitudes and beliefs about HIV/AIDS. General awareness was good, although there were many misconceptions about transmission modes, stigmas and discrimination against HIV positive persons. Knowledge was significantly determined by schooling, residence and sex. Although they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 0 publications
1
9
2
Order By: Relevance
“…Contextual factors play an important role in our study, an aspect that is inadequately addressed in HIV stigma research [54]. Our findings corroborate the notion that HIV stigma in low-HIV prevalence and low-resource communities [59,60]. Funding for HIV programs is usually scarce, professionals' contact with PLHIV is uncommon [23,61], and HIV knowledge is poor in these contexts [51,54].…”
Section: Discussionsupporting
confidence: 78%
“…Contextual factors play an important role in our study, an aspect that is inadequately addressed in HIV stigma research [54]. Our findings corroborate the notion that HIV stigma in low-HIV prevalence and low-resource communities [59,60]. Funding for HIV programs is usually scarce, professionals' contact with PLHIV is uncommon [23,61], and HIV knowledge is poor in these contexts [51,54].…”
Section: Discussionsupporting
confidence: 78%
“…This study showed that the adult population in Mizoram had good overall HIV/AIDS knowledge, but that there were significant gaps among those who lived in rural areas, from poor households, who were illiterate, with no schooling, from a non-Christian faith, belonging to other backward class, and those who had no exposure to media. A similar study in Yemen [ 7 ] also found that rural dwellers and those with no schooling had significantly poorer knowledge of HIV/AIDS. Similarly, a study in India [ 22 ] found HIV transmission and prevention knowledge was low among women and rural residents.…”
Section: Discussionmentioning
confidence: 76%
“…The analyses were guided by previous studies [ 7 , 14 , 15 ], especially from low-and middle-income countries, which played a role in the potential confounding factors selected for the study and were classified into three levels: individual-, household- and community-level factors. Individual-level factors were respondents’ gender, working status, education, age, religion, and marital status.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings were reported from India by Kermode, Holmes, Langkham, Thomas, and Gifford (2005), who examined HIV-related knowledge, attitudes, and risk perception among nurses, physicians, and other health care providers. The negative attitudes of health care providers increase the burden on people living with AIDS and reinforce the stigma they experience (Al-Serouri, Takioldin, Oshish, Aldobaibi, & Abdelmajed, 2002).…”
mentioning
confidence: 99%